PARENTING PATTERNS IN FORMING ISLAMIC CHARACTER IN EARLY CHILDREN THROUGH INDEPENDENT LEARNING ACTIVITIES IN RA AL-IKHLAS KONGGO, SUNGGAL DISTRICT, DELI SERDANG DISTRICT - Nofianti, Rita; Panggabean, Hadi Saputra; Rambe, Almanah (Proceeding International Seminar of Islamic Studies, 2024)
Parents are the first people who play a very big role in building a child's life. Parents are the initial social environment known to the child, the figures who determine the quality of a child's life, and the figures closest to him, both physically and psychologically. Therefore, parents must pay more attention to the parenting style given to children to shape character from an early age, so that after the child grows up, he will grow into a human being with the character that is expected. The aim of this research is to find out parenting patterns in the formation of Islamic character in early childhood through independent learning activities at Ra Al-Ikhlas Konggo, Deli Serdang Regency. Meanwhile, the benefit of this research is as a contribution of thought to help parents solve problems related to authoritarian parenting patterns in shaping the character of early childhood. The method in this research is descriptive qualitative. The results of this research are that parents' parenting patterns have formed the character of early childhood, and the parenting pattern applied is a democratic parenting pattern, because a democratic parenting style pays attention to and respects children's freedom. Factors that influence the development of children's Islamic character formation include internal and external factors.